2007
DOI: 10.1111/j.1742-4658.2007.05804.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of NF‐κB subunit p65 and retinoic acid receptors, RARα and RXRα, in transcriptional regulation of the human GnRH II gene

Abstract: In humans, the genes for gonadotropin-releasing hormones (GnRH I and GnRH II) have the same modular structure, harboring three introns and four exons. The exons encode a precursor polypeptide consisting of a signaling peptide, the GnRH decapeptide, and the GnRH-associated peptide (GAP) with unknown function [1]. The promoter region of the human (h)GnRH II gene is located at the 5¢ flanking region, the untranslated exon 1, intron 1, and exon 2. The locations of exon 1, intron 1 and exon 2 are )793 ⁄ )750 (relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The presence of RAREs of the DR2 and DR5 types in the promoter region of retinoid-responsive genes are often a signature for those genes that respond directly, and often very rapidly, to RA or to other retinoid receptor agonists [20, 29]. However, RA -activated RAR receptors may also interact with other nuclear receptors such as AP1 [3033], NFκB [34, 35], SP1 [3640], and Nrf2 [41], and these may also regulate the expression of genes containing DNA sequences for these proteins. Balmer and Blomhoff [19] reported that whereas about 530 genes are known to be regulated by RA, only a few dozen of have definitively been shown to be directly regulated by RA.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of RAREs of the DR2 and DR5 types in the promoter region of retinoid-responsive genes are often a signature for those genes that respond directly, and often very rapidly, to RA or to other retinoid receptor agonists [20, 29]. However, RA -activated RAR receptors may also interact with other nuclear receptors such as AP1 [3033], NFκB [34, 35], SP1 [3640], and Nrf2 [41], and these may also regulate the expression of genes containing DNA sequences for these proteins. Balmer and Blomhoff [19] reported that whereas about 530 genes are known to be regulated by RA, only a few dozen of have definitively been shown to be directly regulated by RA.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, competition for DNA NF-kB response elements between NF-kB and other transcription factors may occur. This was shown for the same sequence in the promoter of the human GnRH II gene for p65 and RARa/RXRa (47). However in FTC cells, neither could we detect RXR in the p65 transcriptional complex by ChIP nor RXR/p65 interaction by coimmunoprecipitation.…”
Section: Before Treatmentmentioning
confidence: 97%
“…Therefore, xenobiotic chemicals could affect GnRH neural functions through xenobiotic receptors. However, transcriptional regulation of GnRH genes via xenobiotic nuclear receptors has only been demonstrated in vitro in neuronal culture cells [30][31][32], but not in vivo in the brain.…”
Section: Introductionmentioning
confidence: 99%